Analysis and verification on one-dimensional location performance of shortwave single station - Ting LI (Dianxin kexue)
With the low sensitivity of beam field and noise-sensitive of high resolution spatial spectrum algorithm,the low location precision under the complex electromagnetic environment becomes a severe problem.The Capon and Root-MUSIC (CRMU) joint algorithm was proposed to research the one-dimensional location technology.The proposed algorithm could not only avoid the high operation caused by the peak search but also suppress the noise,which contributed to reduce the root mean square error (RMSE) of azimuth.Then,the simulation results demonstrate that the RMSE of the proposed algorithm is at least 0.2 degrees less than that of the Root-MUSIC algorithm.In addition,the location error of the proposed algorithm is less than 3% in the practical application of one-dimensional location of shortwave single station,which satisfies the demand that the location error should be below 5%.